Kirk-Othmer Encyclopedia of Chemical Technology 2000
DOI: 10.1002/0471238961.0914151807181520.a01
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical Processing, Inorganic

Abstract: Electrochemical processes are used to produce an array of reactive inorganic chemicals and metals. The most reactive materials, strongest oxidants, and strongest reductants are produced electrochemically at anodes and cathodes, respectively. Process technology for the production of each electrochemical is unique. Power supplies and electrolytic cells are the distinguishing features of electrochemical processes. Electrolytic cells use direct current and are designed to be process specific. Every cell consists o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…On the interior base of each cell, narrow bracket supports extended the length of the cell. On the top of each support bracket, a narrow slit was cut; into this slit, narrow ribbons of titanium anode, coated with a proprietary coating 1 of ruthenium oxide and titanium dioxide (Grotheer, 1998), were mounted perpendicular to the cathodes. Each cell had 40 ribbons, each 0.5 cm apart from the other.…”
Section: Methodsmentioning
confidence: 99%
“…On the interior base of each cell, narrow bracket supports extended the length of the cell. On the top of each support bracket, a narrow slit was cut; into this slit, narrow ribbons of titanium anode, coated with a proprietary coating 1 of ruthenium oxide and titanium dioxide (Grotheer, 1998), were mounted perpendicular to the cathodes. Each cell had 40 ribbons, each 0.5 cm apart from the other.…”
Section: Methodsmentioning
confidence: 99%
“…The range of examples exploiting electrocatalytic steps in organic synthesis is significantly smaller in volume than thermochemical analogues. 41–44 However, it has been demonstrated that there is substantial market potential to implement electrosynthetic routes as an alternative to traditional thermochemical approaches, for the sustainable production of organic chemicals, such as is the case with the Simons fluorination process, 45 the Monsanto adiponitrile process, 46 and electrochemical deuteration methods. 47…”
Section: Beyond Small Molecule Activation: Sac-driven Organic Electro...mentioning
confidence: 99%
“…Good electrolyte circulation provides transport of electro-active species to the electrode surface as well as taking bubbles away from the electrode surface. Internal gas lift circulation in a welldesigned electrochemical cell is much more efficient than mechanically pumped circulation [11]. In this article, the effect of gas-lift circulation on the texturing process of silicon wafers has been studied.…”
Section: Introductionmentioning
confidence: 99%